The effect of magnesium and vitamin E pre-treatments on irradiation-induced oxidative injury of cardiac and pulmonary tissues in rats: a randomized experimental study - ATASOY, BESTE MELEK; BOSTANCI, KORKUT; YÜKSEL, MERAL (TURKISH SOC CARDIOLOGY, 2012)
Objective: The aim of this study was to investigate the effect of pre-treatment with the free radical scavenging molecules, magnesium and vitamin E, on lipid peroxidation to limit radiation-induced heart and lung injury. Methods: Female Sprague-Dawley rats were divided into 4 groups by a simple randomization method as saline-treated control (n=4), saline-treated irradiated (IR; n=6), magnesium sulphate-treated irradiation (IR) (Mg+IR; n=6) and vitamin E-treated IR (vit E+IR; n=6), respectively. The animals were given either saline, Mg (600mg/kg/day) or vit E (100 mg/kg/day) intraperitoneally for five days prior to irradiation. Twelve hours after the fifth injection, animals in irradiation groups were irradiated to 20 Gy using 6 MV photons in linear accelerator. Twenty-four hours later cardiac and lung tissue samples were obtained for determination of myeloperoxidase activity (MPO), malondialdehyde (MDA) levels, and luminol and lucigenin levels measured by chemiluminescence (CL) methods. Results: No significant changes were observed between cardiac and pulmonary MDA and CL results of the experimental groups. However, cardiac and pulmonary MPO activities in the saline-treated IR group were increased as compared to control group (p<0.05 for all), while in the Mg-pretreated and vit E pretreated groups neutrophil infiltration was reduced, reaching to statistical significance only in the Mg-pretreated group (p<0.05). Conclusion: Prophylactic use of magnesium sulfate has limited the infiltration of neutrophils to both the cardiac and pulmonary tissues at the early 24 h of irradiation. However, how limiting neutrophils as the sources of free radicals and inflammatory mediators would alter oxidative stress of heart and lung tissues in the long-term is not clear yet. (Anadolu Kardiyol Derg 2012; 12: 508-14)
Keywords: Heart; irradiation; lung; magnesium; radioprotection; vitamin E; BREAST-CANCER; HEART-DISEASE; REACTIVE OXYGEN; FOLLOW-UP; IN-VITRO; RADIATION; RADIOTHERAPY; AMIFOSTINE; MYELOPEROXIDASE; SURVEILLANCE